(untitled) (Journal of Contemporary Issues in Accounting, 2026)
The challenge of achieving optimal balance between liquidity maintenance and profitability maximization remains a critical concern for Nigerian deposit money banks, necessitating empirical investigation into how liquidity management practices affects financial performance outcomes. This study ascertained the effect of liquidity management on financial performance of quoted deposit money banks in Nigeria. The study was anchored on Trade-off Theory. The study employed ex-post facto design using panel data from ten quoted deposit money banks over a ten-year period spanning 2015-2024, extracted from audited annual financial statements. Panel Estimated Generalized Least Squares was utilized for data analysis. The findings revealed that current ratio had a positive and significant effect on return on assets (coefficient = 0.016915, p-value = 0.0317), while cash reserve ratio demonstrated a highly significant positive relationship (coefficient = 0.624781, p-value = 0.0000). The study concluded that effective liquidity management significantly enhanced financial performance of quoted deposit money banks in Nigeria through strategic balance of competing objectives. The study recommended among others that bank management should implement prudent current ratio management strategies by maintaining optimal levels of current assets relative to current liabilities, and that regulatory authorities and bank executives should strengthen cash reserve ratio policies by ensuring adequate liquidity buffers while simultaneously creating investment opportunities that allowed banks to maintain required reserves without significantly compromising their income-generating capacity..